A Qualitative Study of Students’ Interest, Learning Difficulty, and Teachers’ Teaching Methods in Geography in Secondary Schools of Meghalaya - Sarif, Md Nawaz; khardewsaw, Meralis; Vandana, (JOURNAL OF INDIAN EDUCATION, 2020)
Geography is one of the core school subjects in India. As a school subject, it has also gained its due place in the Secondary School Leaving Certificate (SSLC) syllabus, Meghalaya. There is a general notion that geography is a tough subject in the social sciences. This notion may exist due to several related factors that hamper geography learning in schools. In this connection, the present study was undertaken to explore the students’ interests and learning difficulty in geography and to analyse the methods employed by teachers to teach geography. In this study, a qualitative research design was used and a self-developed semi-structured questionnaire was employed to collect data from fifty-seven secondary school students and twelve teachers in the South West Khasi Hills district of Meghalaya. The analysis was completed based on frequency, percentage, and content analysis. The findings showed that the majority of students (N=42, 73.68%) had an interest in geography. However, a significant proportion of the students (N=15, 26.32%) did not like the subject. Furthermore, the study rendered the grounds of students’ interest and disinterest in the subject. Besides, different areas related to students’ learning difficulty were identified. For better off, the study urged teachers to use innovative and ICT integrated methods and teaching aids in the classroom. Teachers’ training and content mastery for teachers was emphasised as essential criteria for effective and interesting teaching at school levels.